1988
DOI: 10.1037/0022-0167.35.2.183
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of Holland's personality types to educational satisfaction with a Native-American high school population.

Abstract: We examined the relation of Holland's personality typologies and satisfaction with education, using a sample of 596 Native-American high school students enrolled in eight schools in Manitoba, Canada. We used the Self-Directed Search to determine personality typologies and the Teacher Approval and Education Acceptance scales of the Survey of Study Habits and Attitudes to measure educational satisfaction. Results of analysis of variance showed that students with an Investigative or Social personality type code h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Similarly, Lent (2004) suggested that work and academic satisfaction share comparable antecedents. Factors such as personality type (Gade, Fuqua, & Hurlburt, 1988), calling (Duffy, Allan, & Dik, 2011), learning approaches (Sheard & Golby, 2007), goal progress (DeShields, Kara, & Kaynak, 2005), development of skills (Lizzio, Wilson, & Simons, 2002), self-efficacy (DeWitz & Walsh, 2002), and environmental support (Lent et al, 2007) are suggested to influence academic satisfaction. Although academic satisfaction might be an important end in itself, it is related to important outcomes such as educational persistence, reduced withdrawal from the chosen course of study (Lent et al, 2007), and life satisfaction (Lent, Taveira, Sheu, & Singley, 2009).…”
Section: Academic Satisfactionmentioning
confidence: 99%
“…Similarly, Lent (2004) suggested that work and academic satisfaction share comparable antecedents. Factors such as personality type (Gade, Fuqua, & Hurlburt, 1988), calling (Duffy, Allan, & Dik, 2011), learning approaches (Sheard & Golby, 2007), goal progress (DeShields, Kara, & Kaynak, 2005), development of skills (Lizzio, Wilson, & Simons, 2002), self-efficacy (DeWitz & Walsh, 2002), and environmental support (Lent et al, 2007) are suggested to influence academic satisfaction. Although academic satisfaction might be an important end in itself, it is related to important outcomes such as educational persistence, reduced withdrawal from the chosen course of study (Lent et al, 2007), and life satisfaction (Lent, Taveira, Sheu, & Singley, 2009).…”
Section: Academic Satisfactionmentioning
confidence: 99%
“…A parallel, conceptually related research track has involved the study of educational or academic satisfaction (i.e., enjoyment of one's role or experiences as a student). Although academic satisfaction has not garnered quite the same intensity of inquiry as has job satisfaction, psychological and educational researchers have examined a host of factors, such as Holland personality type (Gade, Fuqua, & Hurlburt, 1988), self-efficacy (DeWitz & Walsh, 2002), and goal progress (DeShields, Kara, & Kaynak, 2005), that may be relevant to the experience of academic satisfaction.…”
mentioning
confidence: 99%